COMPARISON OF ALTERNATIVE SHIP-TO-YARD VEHICLES WITH THE CONSIDERATION OF THE BATCH PROCESS OF QUAY CRANES - Choi, Sang-Hei; Won, Seung Hwan; Lee, Chulung (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
Container terminals around the world fiercely compete to increase their throughput and to accommodate new mega vessels. In order to increase the port throughput drastically, new quay cranes capable of batch processing are being introduced. The tandem-lift spreader, equipped with a quay crane, which can handle one to four containers simultaneously has recently been developed. Such increase in the handling capacity of quay cranes requires significant increase in the transportation capacity of ship-to-yard vehicles as well. The objective of this study is to compare the performances of three alternative configurations of ship-to-yard vehicles in a conventional container terminal environment. We assume that the yard storage for containers is horizontally configured and the quay cranes equip with tandem-lift spreaders. A discrete event simulation model for a container terminal is developed and validated. We compare the performances of the three alternatives under different cargo workloads and profiles, represented by different annual container handling volumes and different ratios of tandem mode operations, respectively. The results show that the performances of the alternative vehicle types are largely dependent on workload requirement and profile.